SIFAT VENIR DAN KAYU LAPIS SEMBILAN JENIS KAYU BERASAL DARI KALIMANTAN BARAT DAN JAWA BARAT - Suwandi Kliwon; M I Iskandar; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1991)
This paper presents study   result on the log peeling properties  and the glueing,  physical and mechanical properties of the veneer and plywood  made from nine wood species are described in this paper. The result shows that all of the, logs could be peeled in cold condition. The average veneer shrinkage from green to oven dry moisture content was 7.00 % and veneer swelling from oven dry to air dry  condition the average value was 3.39 %. The average thickness reduction due to pressing in plywood manufacturing was  3. 78 mm. The  bonging strength of plywood  from 8  wood species (89 %)  conforms  with the Indonesian standard  for  type  II, 9 wood species  (100 %)   with Japanese standard and 9 wood species (100 %)  with German standard.  The average specific gravity  of multiplex  was 0.61 while the average specific gravity of trplex was  0.60. Bending strength. tensile strength and compression  strength parallel to grain of triplex are higher  than multiplex.